NATO and Germany : a study in the sociology of supranational relations - Lyman, Stanford M. (Studies in American sociology ;, 1995)
Focusing on the Cold War years, this monograph examines the processes, problems, and policies through which the Federal Republic of Germany was formed and admitted into the North Atlantic Treaty Organization (NATO). The author compares the situation of Weimar Germany during its short-lived postwar decade with that of the Federal Republic by applying geopolitical concepts and theory, illustrating Germany's territorial uniqueness and how that special aspect of its place on the European continent influenced the nation's diplomacy in both eras.